2021
DOI: 10.5455/sajem.040212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Pediatric Tuberculosis, Presenting to the Emergency Department of Tertiary Care Hospital in Karachi, Pakistan.

Abstract: Background Tuberculosis (TB), a preventable airborne infectious disease, early detection is essential to improve health outcomes. Extent of childhood tuberculosis is unknown and is estimated to be around 6% of all incidences. Diagnosis of pediatric tuberculosis is always difficult and no age is spared, however, children <5 years are more at risk. Children frequently admitted through emergencies of hospitals with different working diagnoses and later diagnosed as tuberculous. Despite multiple studies from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…This finding is contrasted with the German study which reported a high median score in all the physical domains and global scales 43 . Moreover, previous studies reported that most colorectal cancer patients had good HRQoL in the global score 44,45 . These disparities in HRQoL between our setting and other studies are likely attributable to differences in the quality of care, stage of disease, and co‐morbidity.…”
Section: Discussioncontrasting
confidence: 97%
“…This finding is contrasted with the German study which reported a high median score in all the physical domains and global scales 43 . Moreover, previous studies reported that most colorectal cancer patients had good HRQoL in the global score 44,45 . These disparities in HRQoL between our setting and other studies are likely attributable to differences in the quality of care, stage of disease, and co‐morbidity.…”
Section: Discussioncontrasting
confidence: 97%